Competency and the learning organization - Shandler, Donald (Crisp Publications Menlo ParkUS, 2000)
Provides guidelines for implementing the competency-based learning (CBL) programme, beginning at building a foundation, through designing the curriculum, implementing, measurement, and evaluation stages. Provides practical examples of organizations which have sucessfully implemented the programme. Looks at topics including: assumptions about adult learners; role of the project team; role of the supervisor; and self-directed learning implementation.